PENGARUH MODEL PEMBELAJARAN CTL MEDIA PEMBELAJARAN MARKET PLACE ACTIVITY MATEMATIKA TERHADAP KEMANDIRIAN SISWA - Azizah, Siti Nur (JUSEDA, 2023)
This research aims to analyze the influence of the Contextual Teaching and Learning (CTL) model using the "Market Place Activity" learning media on students' independence in learning mathematics. This research uses a mixed methods approach with a sequential explanatory design. Data collection is done quantitatively and qualitatively. Quantitative data is collected through pre-tests and post-tests, testing for normality using paired t-tests and gain tests. Qualitative data is collected through observations and interviews with the students. The research subjects are 30 students from grade 1. The results of this research show that the quantitative data is normally distributed with a significant value of 0.187 > 0.05 for the pre-test and 0.080 > 0.05 for the post-test. Then, the paired sample t-test yields a significant 2-tailed result of 0.00 This indicates that the difference is not occurring by chance. Furthermore, the gain test yields a significant mean value of 0.8789, indicating that the average test results are at a high level. The observation results show that using the CTL model with the MPA learning media in mathematics enables students to become more active in their learning. The interview with the students also reveals that the use of the CTL model with the MPA media helps students understand the learning material and promotes their independence in the learning process. This research concludes that the use of the CTL learning model with the market place activity learning media has a positive influence on students' independence in learning mathematics.